Pendampingan Jemaat GKSI Makarios dalam Penanganan Konflik dan Penguatan Pertumbuhan Rohani Berdasarkan 1 Petrus 5:2–3 - Darius kahabi Raumbani (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
In life as a congregation and as servants of God, we cannot escape conflict within the church. Sometimes, conflict is inevitable within a church. This is because sometimes things start out fine, but when conflict arises, each individual makes their own decisions. Some choose to remain on the other side, while others choose to leave the fellowship. This article aims to explain the factors that cause divisions in the church, specifically the GKSI Makarios church, and what actions God's servants should take when faced with such a situation. Of course, this article uses two sources to resolve this issue, namely interviews and data such as books or other reading sources that discuss similar events related to the topic. It is hoped that this article will be a valuable lesson for ministers and congregations in dealing with every situation in the church. It is important to discuss this topic in order to educate readers that disputes are inevitable in church organizations. Therefore, when joining a community, it is important to consider the best solutions for dealing with disputes so that one does not act rashly when trying to resolve problems properly.